2019
DOI: 10.1016/j.cis.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

A practical review on the measurement tools for cellular adhesion force

Abstract: Cell-cell and cell-matrix adhesions are fundamental in all multicellular organisms. They play a key role in cellular growth, differentiation, pattern formation and migration. Cell-cell adhesion is substantial in the immune response, pathogen-host interactions, and tumor development. The success of tissue engineering and stem cell implantations strongly depends on the fine control of live cell adhesion on the surface of natural or biomimetic scaffolds. Therefore, the quantitative and precise measurement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 226 publications
(565 reference statements)
0
82
0
1
Order By: Relevance
“…Here, we studied the adhesive capacity of MDMs and MDDCs after LPS stimulation. We used both the classical, end-point adhesion assay and a computer-controlled micropipette method capable of measuring the force of adhesion [71]. When applying ligand binding site specific antibodies, we found that both anti-CD11b and anti-CD11c treatment weakened the adhesion to fibrinogen coated surfaces, as verified by the decreased number of adherent cells as well as the force of attachment.…”
Section: Plos Onementioning
confidence: 99%
“…Here, we studied the adhesive capacity of MDMs and MDDCs after LPS stimulation. We used both the classical, end-point adhesion assay and a computer-controlled micropipette method capable of measuring the force of adhesion [71]. When applying ligand binding site specific antibodies, we found that both anti-CD11b and anti-CD11c treatment weakened the adhesion to fibrinogen coated surfaces, as verified by the decreased number of adherent cells as well as the force of attachment.…”
Section: Plos Onementioning
confidence: 99%
“…Over the years, numerous methods have been introduced to examine and quantify cell adhesion, from simple observations in an optical microscope to increasingly elaborate atomic force microscopy (AFM) techniques [15][16][17][18][19] . These techniques either measure cell-surface interactions and cell adhesion kinetics 10,[20][21][22][23][24] , or they are based on applying a force that can lead to cell detachment (termed adhesion strength measurements) on single-cells (e.g., micropipette aspiration, AFM, optical tweezer techniques) or on cell populations (e.g., centrifugation assay, spinning disk, flow chamber) 25 . One critical parameter of cell adhesion measurement methods is the throughput, describing the number of cells that can be detached in a certain period of time 26 .…”
mentioning
confidence: 99%
“…There are several ways to evaluate directly the cellular adhesion strength [ 84 ]. Bulk experiments are the most commonly used methods, which involve growing the cells on the substrate, exposing them to a buffer which produces cell detachment, and monitoring the percentage of cells which are capable of maintaining their adhesion to the surface.…”
Section: Tic Layers Obtained Using Pulsed Laser and Ion Plated Plamentioning
confidence: 99%